Targeting Stress-Response Pathways and Therapeutic Resistance in Head and Neck Cancer - Bos, Tasia; Ratti, J. Alex; Harada, Hisashi (Frontiers in Oral Health, 2021)
Head and neck cancer is the sixth leading cancer worldwide; head and neck squamous cell carcinoma (HNSCC) accounts for more than 90% of incident cases. In the US, cases of HNSCC associated with human papillomavirus (HPV) have been growing in proportion amongst a younger demographic with superior outcomes to the same treatments, relative to cases associated with tobacco. Yet failures to improve the long-term prognosis of advanced HNSCC over the last three decades persist in part due to intrinsic and acquired mechanisms of resistance. Deregulation of the pathways to respond to stress, such as apoptosis and autophagy, often contributes to drug resistance and tumor progression. Here we review the stress-response pathways in drug response and resistance in HNSCC to explore strategies to overcome these resistance mechanisms. We focus on the mechanisms of resistance to current standard cares, such as chemotherapy (i.e. cisplatin), radiation, and cetuximab. Then we discuss the strategies to overcome these resistances, including novel combinations and immunotherapy.